Elementary fluid mechanics - Vennard, John K. (John Wiley, 1961)
Fluid mechanics is the study of fluids under all conditions of rest and motion. Its approach is analytical and mathematical rather than empricial; it is concerned with the basic printciples which allow the solution of the numerous and diversified problems encountered in many fields of engineering irrespective of the physical properties of the fluids involved